Hubungan Antara Kepribadian Big Five dan Kecerdasan Emosional pada Mahasiswa Program Studi Kedokteran Fakultas Kedokteran Universitas Tanjungpura - Praditiani, Ririn; Wilson, Wilson; Hermawati, Ery (Sci-tech Journal, 2025)
Personality describes characteristics that are relatively permanent in individuals and will affect the behavior of these individuals. Personality is one of the factors that can affect a person's emotional intelligence. The low emotional intelligence of a person will have an impact on a person’s emotional mental cindition such as anxiety, stress, depression. The purpose of this study was to determine the relationship between the Big Five personality and emotional intelligence in students of the Medical Study Program, Faculty of Medicine, Tanjungpura University. The research method used in this study was an analytical observational design with a cross-sectional approach. The research population was students of the Medical Study Program, Faculty of Medicine, Medical University who were selected using the cluster random sampling method with 169 subjects. Bivariate analysis using Spearman correlation test with SPSS 24.0The results by the Spearman correlation test obtained a significance value of 0.000 (Sig <0.05) for the relationship between the personality Big Five and emotional intelligence in students of the Medical Study Program, Faculty of Medicine, Tanjungpura University. There is a relationship between the Big Five personality and emotional intelligence in Medical Study Program Students, Faculty of Medicine, Tanjungpura University.